Righteous anger: in contemporary Italian literary and cinematic narratives - Lucamante, Stefania (Toronto Italian studies, 2020)
Pasolini's La rabbia and the Spectacularization of Scarpa's Posthuman Aesthetics -- An Apocalyptic Kamikaze: Tiziano Scarpa or How to Invade the Reader -- The Fundamental Things in Life According to Scarpa -- Melania Mazzucco's Un giorno perfetto: Domestic Violence on an Everyday Perfect Day -- Pushing Boundaries: Road Movies and Gas Stations in Monica Stambrini's Benzina -- A Recipe for the Advantages and Disadvantages of Love: Anger and Misogyny in Paolo Sorrentino's The Consequences of Love -- Society, Simulacra, and Love: Simona Vinci's Stanza 411 -- Wounding the Individual: Dynamics of Diversity and Anatomy of Love in Veronica Tomassini's Sangue di Cane.